1984
DOI: 10.1128/iai.43.3.1006-1011.1984
|View full text |Cite
|
Sign up to set email alerts
|

Nonopsonic phagocytosis of strains of Pseudomonas aeruginosa from cystic fibrosis patients

Abstract: Pseudomonas aeruginosa is the predominant respiratory pathogen in patients with cystic fibrosis, but its Mechanism of persisting in pulmonary secretions is poorly understood. We observed that three nonmucoid cystic fibrosis P. aeruginosa strains were phagocytized and one strain resisted phagocytosis by human polymorphonuclear leukocytes in the absence of serum. Phagocytosis was assessed by luminol-enhanced chemiluminescence, inspection of stained smears, bactericidal assay, reduction of nitroblue tetrazolium d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
38
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(42 citation statements)
references
References 9 publications
3
38
0
Order By: Relevance
“…The overall biological role of this mucoid exopolysaccharide (MEP) of P. aeruginosa remains incompletely defined. It appears that this alginic acid MEP mediates attachment of pseudomonal strains to tracheal epithelium (25), interferes with effective complement-driven PMN chemotaxis (31), renders mucoid variants less susceptible to nonopsonic phagocytosis by macrophages (9,11,29), and assists the organism in resisting oxidative intracellular killing via the myeloperoxidase system through 'hypochlorite scavenging' (16). The other putative major function of MEP is to interfere with intracellular antibiotic accumulation, presumably via barrier mechanisms, with resultant diminution of antibiotic-induced growth inhibition and killing.…”
mentioning
confidence: 99%
“…The overall biological role of this mucoid exopolysaccharide (MEP) of P. aeruginosa remains incompletely defined. It appears that this alginic acid MEP mediates attachment of pseudomonal strains to tracheal epithelium (25), interferes with effective complement-driven PMN chemotaxis (31), renders mucoid variants less susceptible to nonopsonic phagocytosis by macrophages (9,11,29), and assists the organism in resisting oxidative intracellular killing via the myeloperoxidase system through 'hypochlorite scavenging' (16). The other putative major function of MEP is to interfere with intracellular antibiotic accumulation, presumably via barrier mechanisms, with resultant diminution of antibiotic-induced growth inhibition and killing.…”
mentioning
confidence: 99%
“…More precisely, the liver clears bacteria and other particulates via the hepatic reticuloendothelial system in which Kupffer cells, resident macrophages, are strategically situated to perform this function because they are located in the periportal region where blood enters the liver. Nonopsonic phagocytosis by Kupffer cells, such as lectinophagocytosis and hydrophobic interaction, is an important mechanism in the clearance of bacteria from the blood flow and in host defense against bacteremia (Speert et al, 1984). Recently, it has been reported that hepatic bacterial clearance is preserved throughout the evolution of mild bacteremia but is lost late with severe bacteremia (Ashare et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…A number of different immune cells are involved in effective host defense to P. aeruginosa. Much work has demonstrated the importance of alveolar macrophages and polymorphonuclear neutrophils in the phagocytic killing of P. aeruginosa [1,32,33]. Clearly, however, our knowledge of the in vivo immune response to P. aeruginosa is incomplete.…”
Section: Discussionmentioning
confidence: 99%
“…This opportunistic organism has a number of virulence factors that enable it to circumvent the immune response and therefore evade clearance by the host. A number of investigators have emphasized the role of nonspecific immunity in defense to P. aeruginosa infection [1,2] and yet the events involved in perpetuating the infection, despite the presence of phagocytic effector cells, remain unclear.…”
Section: Introductionmentioning
confidence: 99%